(untitled) (Journal of Hama University, 2021)
This study aims to investigate the Seismic response behavior of concrete buildings with interactive structural systems consisting of (shear walls and frames), which containing a single solid Transfer slab in one of its floors , with 10-20-30-50%.of total height of building, Studying building, Studying relative changes in the inter story Drifts. This slab is a Flat solid plate in which supports the elements above, whereas don’t continue underneath of it in a Certain part of the floor that is to form large areas below this slab, so the architectural requirement is the main need of it and as the architectural designs require the presence of large halls on one of the floors of high buildings. Hence, it was necessary to study the effect of the placements of this slab and give a preliminary concept to the designers to later choose the site that matches the nature of the building design. As a result of this slab with a huge mass which placed in a particular floor and whose presence changes the distribution of the lateral resisting elements , all of these will form a vertical irregularity in the Structural system. Therefore, advanced dynamic methods were chosen to calculate the inter-story Drifts, seismic analysis depending on the dynamic response spectrum UBC 97, and Nonlinear Time History of (Chi-Chi 1999) record, and accordingly the maximum relative changes of inter-story Drifts were found in levels of the slab 10-50%.H and Relatively least, with levels of 20-30% and more ductility demand.